Altered dynamic intrinsic brain activity of the default mode network in Alzheimer’s disease: A resting-state fMRI study - Liao, Zhengluan; Sun, Wangdi; Liu, Xiaozheng; Guo, Zhongwei; Mao, Dewang; Yu, Enyan; Chen, Yan (Frontiers in Human Neuroscience, 2022)
Objective: Static regional homogeneity (ReHo) based on resting state functional magnetic resonance imaging (rs-fMRI) has been used to study intrinsic brain activity (IBA) in Alzheimer’s disease (AD). However, few studies have examined dynamic ReHo (dReHo) in AD. In this study, we used rs-fMRI and dReHo to investigate the alterations in dynamic IBA in AD patients to uncover dynamic imaging markers of AD. Method: One hundred eleven AD patients, twenty-nine mild cognitive impairment (MCI) patients and seventy-three healthy controls (HCs) were recruited for this study ultimately. After the rs-fMRI scan, we calculated the dReHo values using the sliding window method. ANOVA and post hoc two-sample t tests were used to detect the differences among the three groups. We used the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) to evaluate the cognitive function of the subjects. The associations between the MMSE score, MoCA score and dReHo were assessed by Pearson correlation analysis. Results: Significant dReHo variability in the right middle frontal gyrus (MFG) and right posterior cingulate gyrus (PCG) was detected in the three groups through ANOVA. In post hoc analysis, the AD group exhibited significantly greater dReHo variability in the right MFG than the MCI group. Compared with the HC group, the AD group exhibited significantly increased dReHo variability in the right PCG. Furthermore, dReHo variability in the right PCG was significantly negatively correlated with the MMSE and MoCA scores of AD patients. Conclusion: Disrupted dynamic IBA in the DMN might be an important characteristic of AD and could be a potential biomarker for the diagnosis or prognosis of AD.